IMPLEMENTASI JARINGAN WLAN MENGGUNAKAN MIKROTIK PADA KANTOR PATRA IFMS TRAINING CENTER - Rustandi, Rustandi; Ririmasse, Thomas Budiman (Jurnal Manajamen Informatika Jayakarta, 2024)
Patra IFMS Training Center has had a wireless LAN (Local Area Network) network but still uses a hotspot network from the provider, which is very easy to access anytime, anywhere and can be enjoyed as long as the hotspot network is within reach. The main challenge in wireless LAN networks is managing human resources and maintaining the network so that it is effective, ensuring good, stable service quality so that there is no speed tug-of-war between other users when conducting online meetings or online training. This research aims to overcome these challenges by implementing additional MikroTik hardware and using user management methods and bandwidth priorities in the WLAN network as well as testing user management methods, bandwidth priorities on the network and MikroTik remote monitoring that will be added to the new network. The results of using MikroTik are very significant after grouping users using a collaborative user management system with bandwidth priorities so that the use of the internet network will be directed. The computer network at the Patra IFMS Training Center Office has installed a VPN and Address List which helps administrators to monitor network usage that is already running.